Implementing IBM Lotus Enterprise Integrator 6 on the IBM e server iSeries Server - Landon, Deb (IBM redbooks., 2003)
This IBM Redbooks publication helps you to implement Lotus Enterprise Integrator (LEI) 6 on the IBM eServer iSeries server. It is targeted for system administrators who plan to implement or upgrade to LEI 6 in their organization. The book provides tips and techniques to help you successfully deploy and administer LEI 6 on an iSeries server. We begin by providing a brief introduction to what's new with LEI 6 and cover some architectural scenarios of how the LEI 6 infrastructure could be implemented in a customer's environment. We then provide detailed information about how to install and administer LEI 6 on the iSeries server. Migrating or upgrading from LEI 3.x is also covered. This book also provides some basic connectivity information about how to connect one iSeries server to another as well as from iSeries to pSeries and xSeries to iSeries. Finally this book provides some working examples of how to use the Advanced RealTime activities that are new in LEI 6. It also provides examples of some of the batch activities previously available in LEI 3.x, such as a scripted activity and a replication activity. Please note that the additional material referenced in the text is not available from IBM.